SPIRITUAL LEADERSHIP IN ISLAMIC EDUCATION (ANALYTICAL STUDY OF THE BOOK OF CHEMICAL OF HAPPINESS AL-GHAZALI) - Siswadi, Siswadi; Jamil, Shobrun (Proceeding International Seminar of Islamic Studies, 2023)
One of the figures who initiated the concept of happiness was al-Ghazali through the chemical of Happiness or kimia as-sa'adah. The purpose of this study is to analyze the book Chemical of Happiness as a guide in the application of leadership in the world of Islamic education. This research is qualitative research with library research methods, while the approach used is a historical and philosophical approach. The historical approach is used to obtain data on social and cultural aspects that occurred during the al-Ghazali period, while the philosophical approach is used to produce data about aspects of Epistemology, Anthology, and Axiology of Chemical of Happinesss. There are two sources of data used by the main data is the book of chemical of Happiness, the second source is a study that discusses leadership from both journals and books. The results of the study found that the chemical of Happiness actualization to spiritual leadership has similarities with al-Ghazali concept of chemical of Happiness, where a leader applies four steps to apply spiritual leadership: First, a leader must know who he is as humankind, so that he acts justly or fair and trustworthily, then knows where a leader comes from, so that the leader should not be arrogant because before Allah he is the same who distinguishes is  his level of devotion, as well as a leader must know where he is going back and will be held accountable for what he leads. Second, a leader must know God by realizing that God is the creator. Third, a leader must know about this world, so that he will prosper the world and the organization he leads well and correctly, Fourth, a leader must know about the afterlife. The implications of al-Ghazali's idea are that a leader who has a spiritual must have metacognition, metaaffection, and metapsychomotor in order to truly become a caliph on the face of this earthKeywords: al-Gazali, spiritual leadership, chemistry of Happiness.